PROYEK OPERASI NASIONAL AGRARIA SEBAGAI UPAYA TERTIB HUKUM PERTANAHAN (Studi di Desa Kesugihan Kecamatan Kesugihan Kabupaten Cilacap) - Triyono, Aryo Danu Kusumo, Hj.Endang Sri Santi, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Rights to land has a very important role in human life, which is the source for the welfare and prosperity. The more dense the population will add another notch importance of land rights. Law No. 5 of 1960 About Basic Agrarian Regulation is a law governing land in Indonesia. The Government's efforts in addressing the interests of the land is to pelaksanaaan Pensertipikatan Land Mass conducted by each region with the implementation of the mechanism dicanangkannya PRONA Agrarian function, it is appropriate that the purpose BAL laying the groundwork for legal certainty regarding land rights for the people entirely.Approach method is empirical juridical approach, the specification using descriptive analytical research, while the population of all parties associated with the program PRONA, and sampling methods are purposive sampling is done by taking the subject and the object based on the specified destination. The data collection methods the authors use the technique of interviewing her (interview) and based on existing data (primary and secondary) that have been collected to allow for qualitative data analysis.Based on the results of the study showed that the implementation of land registration through PRONA Kesugihan village successful and reach the target areas, announced. Although there are still problems facing both facing the Land Office and the community. The problem is the file incomplete petition, proof of ownership of land is not complete and is not legally valid, the lack of technical personnel in the implementation.The registration of land through PRONA in District Kesugihan Village Kesugihan generally well run and managed. Because of the problems that occur can be solved with good efforts is to improve cooperation and coordination between the Land Office with the parties involved, such as the participants PRONA and the local village.